2022
DOI: 10.3389/fnut.2022.1067468
|View full text |Cite
|
Sign up to set email alerts
|

Is there any association between dietary inflammatory index and quality of life? A systematic review

Abstract: BackgroundThe inflammatory potential of unhealthy diets can lead to the development of chronic diseases and also exacerbating their complications. Therefore, the present systematic review aimed to evaluate the association of dietary inflammatory index (DII) and quality of life (QOL) in human subjects.MethodsA systematic search was conducted in PubMed, Web of Science, and Scopus databases, using the combination of all search terms related to DII and QOL until May 2022. All eligible human studies published in En… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 108 publications
0
3
0
Order By: Relevance
“…The microbiome-gut-brain axis, a neural, hormonal, and immunological signaling system, has been extensively described in recent studies ( 9 11 ). However, this interplay is critically influenced by the gut microbiota, whose metabolites and neurochemicals affect brain function and behavior ( 8 , 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…The microbiome-gut-brain axis, a neural, hormonal, and immunological signaling system, has been extensively described in recent studies ( 9 11 ). However, this interplay is critically influenced by the gut microbiota, whose metabolites and neurochemicals affect brain function and behavior ( 8 , 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence supports the relationship between nutritional interventions (NI), nutritional status (NS), and QoL in cancer patients [ 25 ]. The importance of the NI in terms of QoL was also described in a systematic review, which showed that a NI might be associated with a better QoL in humans with different diseases [ 26 ]. Two further studies investigated QoL in cancer patients receiving parenteral nutrition (PN) at home and concluded that this form of PN was associated with an improvement in QoL [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…A pro-inflammatory diet has been linked to an increased cardiovascular risk and mortality [ 20 ], and it increases the likelihood of both metabolic syndrome (MetS) [ 21 ] and various types of cancer [ 22 , 23 , 24 , 25 ]. Recent studies indicate a negative association between a pro-inflammatory diet and HRQoL [ 26 , 27 , 28 ]. A diet associated with low DII scores is the Mediterranean diet (MD) [ 29 ].…”
Section: Introductionmentioning
confidence: 99%